Coping behaviors to stress and self-efficacy of selected public secondary teachers - Serrano, Lea Violeta R. (2005)
This study aimed to determine the coping behaviors to work related stress among teachers in seven public schools in Quezon City and to what extent mediating factors influenced coping behavior. "Stress Profiles for Teachers" developed by Bettie Young was administered to the teachers. The respondents who were vulnerable to stress according the the test were subjected to other instruments used in the study to determine their coping behavior. More than half the respondents were vulnerable to stress and consider work overload as extremely stressful. They engage in adaptive behaviors ang in a less degree, to maladaptive behaviors. There is a significant relationship between coping behavior and self-efficacy.